(3GdJNWjW GdGSJQGJjLj h OhQg aj JMSjf GOGA GdefTBJ GdQjGVjI GdcHQi s - (3bQGHI, ceGds; (3Hf Ycj, eMfO Bcdjs; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2022)
(3JYJHQ GdGOGQI GdQjGVjI QcjRI GSGSjI dfLGM GdSjGSGJ GdYehejI aj bWGY GdQjGVI hJMbjb CgOGa GdJQHjI GdHOfjI hGdQjGVjI GdQGejI Gdi HfGA GdaQO hGdJfTFI GdYGeI aj GdeLJeY(B. (3hjTcd GdJNWjW GdhXjaI GdCSGSjI GdChdi aj GdYedjI GdGOQjI hGdEWGQ GdPj HehLHg JfaP GdhXGFa GdCNQi (B((3GdJfXje , GdJhLjg, GdQbGHI(B)(3, hHaVdg JJMOO GdCgOGa GdJj JSYi GdjgG GdefXeI JMOjOG ObjbG jJeGTi eY GdGecGfjGJ hGdehGOQ GdeJGMI hGdHjFI GdJj JTJZd ajgG(B. (3hGYJHGQG ddecGfI GdGSGSjI GdJj JMJdgG GdefTBJ GdQjGVjI aj GdefXheI GdQjGVjI abO GgJeJ GdOQGSGJ hGdGHMGK aj GdSHd GdcajdI HRjGOI aGYdjI COGFgG HeG jDgdgG ddGSJLGHI dMLe GdfabGJ GdJj JSJgdcgG h JWdYGJ GdeSJajOjf efgG hjQaY ef eSJhi JfGaSjJgG , h JCJj gPg GdOQGSI dJSdW GdVhA Ydi GdYdGbI GdJQGHWjI Hjf GdJNWjW GdGSJQGJjLj haGYdjI GdGOGA HGdefTBJ GdQjGVjI GdcHQi aj GdLRGFQ ef NdGd OQGSI eNJda GdLhGfH GdeJYdbI HGdeNWW GdJhLjgj ddQjGVI hGdEfLGRGJ GdQjGVjI GdcHQi(B- (3GdbGfhfjI hGdGLQGFjI hGdeGdjI (B...- (3HGYJHGQg COGI JhVY aj eJfGhd GdgjFGJ GdeTQaI Ydi EYOGO GdSjGSI GdhWfjI ddGSJeGQ GdYehej aj bWGY GdQjGVI hjMOO NGQWI WQjb Ydi GdeSJhjjf GdeJhSW hGdHYjO dhJjQI GfLGR GdgjGcd GdQjGVjI GdcHQi hGdeYGjjQ GdeYJeOI aj JUejegG hMLegG hJhRjYgG GdLZQGaj hGfOeGLgG eY OjfGejcjI GdJfejI GdJj JTgOgG GdbWGYGJ GdCNQi PGJ GdUdI hHeG jecf CjVG eNJda GdgjFGJ GdQjGVI ef JWhjQ COGFgG hJMbjb CgOGagG aj JYeje GdeeGQSI GdQjGVjI hQaY eSJhi efGaSGJgGGdeMdjI hfJGFLG GdOhdjI(B. (3hJYJeO gP GdOQGSI GdefgL GdhUaj GdJMdjdj aj JfGhd GdehVhY hGdhSGFd GdGMUGFjI GdedGFeI eY gPG GdefgL hGNJjGQ GdYjfI GdJj dgG YdGbI eHGTQI Hcd GdeJONdjf aj YedjI GdJNWjW GdGSJQGJjLj ef GdGOGQI GdYdjG ddOGFQI GdhRGQjI GdecdaI HGdQjGVI hGdGJMGOGJ GdQjGVjI heNJda GdeSJajOjf hGdeJYGedjf (B.s
(3OcJhQGIs
Keywords: (3GOGQI h JSjjQ GdehGQO GdHTQjI h GdefTBJ GdQjGVIs; (3GdGOGQI h GdJSjjQ GdQjGVjs; (3GdJNWjW GdGSJQGJjLjs